Bioremediation of Soil Microcosms from Auto-Mechanic Workshops - AT Ajao; AO Oluwajobi; VS Olatayo (Journal of Applied Sciences and Environmental Management)
Microbial activities are essential for the restoration of soil contaminated with hydrocarbons, their roles includes biotransformation and mineralization of petroleum products into harmless compounds. In this study eighty six soil samples from fifteen auto-mechanic workshops within Ilorin metropolis were collected. These were analyzed by selective enrichment technique, resulted in the isolation of five bacterial species which are Acinetobacter sp, Flavobacterium sp, Pseudomonas sp., Serratia and Bacillus sp. Bioremediation of the soil microcosms was designed for 2months using mixed culture of the isolates. TVC, Protein, Dehydrogenase and lipase activities were used as bioindicators for the bioremediation processes. Highest TVC, Protein and Dehydrogenase activities were recorded in four week as 163.15μgTPFg-1soil,6.3×107and5.53mg/g were obtained respectively at pH of 7.17 and gradually declined while lipase activities and percentage of oil was highest in week six as 65.41% and4.72unit/g. These findings have environmental implication towards developing a bioremediation protocol that could be exploited for cleaning oil polluted soil @JASEM